2013
DOI: 10.1103/physreve.87.062806
|View full text |Cite
|
Sign up to set email alerts
|

Statistical mechanics of multiplex networks: Entropy and overlap

Abstract: There is growing interest in multiplex networks where individual nodes take part in several layers of networks simultaneously. This is the case for example in social networks where each individual node has different kind of social ties or transportation systems where each location is connected to another location by different types of transport. Many of these multiplex are characterized by a significant overlap of the links in different layers. In this paper we introduce a statistical mechanics framework to de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
415
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 325 publications
(418 citation statements)
references
References 52 publications
(81 reference statements)
2
415
0
1
Order By: Relevance
“…The matrix element a [ whether node i is connected to node j in layer α (a [α] ij = 1) or not (a [α] ij = 0). In a multiplex network, we define the total overlap O [α,α ] [37] of the links in layer α and layer α as the total number of pairs of nodes connected both in layer α and layer α ; i.e.,…”
Section: A Multiplex Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…The matrix element a [ whether node i is connected to node j in layer α (a [α] ij = 1) or not (a [α] ij = 0). In a multiplex network, we define the total overlap O [α,α ] [37] of the links in layer α and layer α as the total number of pairs of nodes connected both in layer α and layer α ; i.e.,…”
Section: A Multiplex Networkmentioning
confidence: 99%
“…IV we report the message passing theory for calculating the MCGC in multiplex networks without link overlap, using the formalism of Ref. [37]. In Sec.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in biological systems basic constituents such as proteins can have physical, co-localization, genetic or many other types of interactions. Recently, it has been shown that retaining such multi-dimensional information 7 and modelling the structure of interdependent and multilayer systems respectively through interdependent 8 and multilayer networks [9][10][11][12] reveals new nontrivial structural properties [13][14][15][16][17][18][19][20] and relevant emergent physical phenomena [21][22][23][24][25][26][27] .…”
mentioning
confidence: 99%
“…Therefore, there is a need of modeling these systems as interdependent for understanding their structure, function and robustness [19][20][21][22][23][24][25][26]. Studies on spatially embedded interdependent networks found that in many cases they are significantly more vulnerable then non-embedded systems [27].…”
Section: Introductionmentioning
confidence: 99%